Android-based basic combat learning model - Sari, Desi Purnama; Arifan, Ikhwanul; Mariati, Sari (Department of Coaching, Faculty of Sports Science, Universitas Negeri Padang, Indonesia, 2024)
Problems: This research is motivated by the limited teaching and learning activities of Basic Tarung Derajat in the Department of Sports Coaching, because the lecture hours are only 2 credits limiting student learning activities on campus. Purpose: This research aims to produce a learning product for students as well as in the form of materials / textbooks and an android application that contains Basic Tarung Derajat material in order to create more effective and efficient lectures. The subject of this research is students who take the Basic Tarung Derajat course. Methods: This research was conducted using the Development Research Method, which is a research method used to produce certain products, and test the effectiveness of these products which consist of: (1) Analiyze (observation), (2) Design (designing the Basic Tarung Derajat lecture model), (3) Development (development of the Basic Tarung Derajat lecture model), (4) Implementation (implementation of models that have been made in the form of modules and applications), and (5) Evaluation (the results obtained from the application of the evaluation model of the results of research and models that have been made) then the final TKT is at level 3 Results: The results showed that (1) the development of the Android-based Basic Tarung Derajat learning model was carried out using the Thunkable.apk application named Tarung Derajat Dasar. (2) The validity of the media product gets a percentage of validity by the Material Expert of 70% in the category